A Review of the Stereo lithography 3D Printing Process and the Effect of Parameters on Quality - Mhmood, Tiba Raed; Al-Karkhi, Nazar Kais (Al-Khwarizmi Engineering Journal, 2023)
Stereo lithography (SLA) three-dimensional (3D) printing process is a type of additive manufacturing techniques that uses digital models from computer-aided design to automatically produce customized 3D objects. Around 30 years, it has been widely utilized in the manufacturing, design, engineering, industrial sectors and its applications in dentistry for manufacturing prosthodontics are very important. The stereo lithography technology is highly regarded because it can produce items with excellent precision especially when selecting the best process parameters. This review article offers a useful and scientific summary of SLA three-dimensional printing technology and its brief history. The specific type of 3D printers which is SLA type based on light curing resin and material overview is also presented. Moreover, the survey was conducted to gain substantial knowledge of the various advantages and disadvantages of SLA 3D printing. According to this study, a summary has been specified on the accuracy of SLA 3D printers and various factors that affected its accuracy and dimension measurement namely layer thickness, normal exposure time, bottom or top exposure time, post processing and room temperature. The majority of works in the literatures conducted till date are on improving the physical part attributes like dimensional accuracy and surface roughness but the improving of the mechanical properties have received less attention and need more focusing in the future works.